SIFAT PENGERINGAN ALAMI DAN PENGERINGAN SINAR MATAHARI - Syarif Hidayat; Suparman Karnasudirdja (Pusat Penelitian dan Pengembangan Hasil Hutan, 1985)
The study reported here concerns the drying rate expressed in daily moisture content decrease and the associated defects.Based on moisture content decrease data, the wood species studied were grouped into 3 classes, namely easy, moderately easy and difficult to dry. Easy to dry species include durian burung (Durio carinatus) and mabang (Shorea pachyphylla), moderately easy to dry include meranti bunga (Shorea aliginosa), gerunggang (Cratoxylon arborescens), rengas (Melanorhoea walichii), mengkakal (Callophyllum sculatri), bintangur (Callophyllum sp.), pisangpisang (Mezzetia paviflora) and perupuk (Blumedendron subrotundifolium). Difficult to dry species include resak (Cotylelobium flarum) and empedu (Dryobalanops fusea).Based on drying defects, wood species fall into 3 classes namely light (pisangpisang and mabang), intermediate (meranti bunga, durian burung, rengas,perupuk, bintangur and empedu) and excessive(resak and gerunggang).